Analysis of Heat Balance of the Commutator of Stretch Reducing Mill - Zheng Gang; Zhao Zhengyang; Zhang Yubao (Jixie chuandong)
In order to solve the problem of gear and bearing high temperature burns of the bevel gear commutator of the stretch reducing mill,the heat balance of the bevel gear commutator is analyzed. The thermal network model is established according to the thermal network. The model for calculating heat source power,thermal resistance and heat transfer coefficients are given. Based on principle of thermal network,the heat transfer network calculation model is established by AMESim,and the static temperature field distribution of bevel gear transmission system of commutator is calculated. The no-load test bench is set up to verify the correctness of the model. The results proved the reliability of commutator under the limit working condition,and some advice for assembling according to the distribution of temperature field is given. It is show that test result are basically agreement with the numerical result.